The Influence of Product Image, Product Quality, and Promotion on Repurchase Intention: The of Brand Image as an Intervening Variable on Cimory Yogurt Products - Munir, Alfarizqi Faliq; Kussudyarsana (Jurnal Economic Resource, 2025)
The purpose of this study is to investigate how product quality affects, product image, and promotion on repurchase intention, with brand image serving as a mediating variable in the context of Cimory Yogurt products. Data were gathered from 100 respondents in Solo Raya using a quantitative method, who had consumed Cimory Yogurt in the past three months. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to examine the data. According to the results, repurchase intention is directly and significantly impacted by product image and advertising, but not by product quality. However, product quality, product image, and promotion all have significant indirect effects on repurchase intention through brand image. This study highlights how important brand image is for increasing customer loyalty and implies that managing brand image well can increase the influence of marketing factors on consumer behavior.